Propuesta para la creación de un centro interpretativo cultural en la comunidad Ponce Quilotoa, parroquia Zumbahua - Pastuña Latacunga, Milton Efraín (2023)
The general objective of the research was to develop a proposal for the creation of a cultural interpretation center in the Ponce Quilotoa community, Zumbahua parish. Qualitative research with exploratory scope was used, in this way information was extracted from primary sources through surveys, interviews and field trips to carry out the necessary studies for the implementation of the project. Framed within the qualitative research, the respective processes were developed for each specific objective. Thus, in the market study surveys were applied to visitors of the Quilotoa lagoon through multiple choice questions allowed to establish what activities to propose for the tourist also in the field trip I could observe three direct competitions to the administrators of these places I executed an interview and know the opinion they had about an interpretive center in the parish and to develop a product for tourists who visit, we proceeded with the analysis of the advertising of the center already had the logo by the Association where the facilities of the properties to be used are located, in the technical study of the interpretive center that will have an area of 2. 105.25 m² will have a cozy physical space that will be divided for the exhibition of handicrafts by sections according to the established plans such as; carving room, weaving room, audiovisual room, parking, reception and toilets with conditions suitable for the use of visitors. Currently the infrastructure is already in place and in order to renovate it, approximately $18,186.5 is needed. 186.5 $ that will be assumed by the partners, legal administrative parameters were executed containing a planning of how will be the interpretive center that contains mission, vision, values and policy that will be fulfilled by the partners, The organization contains how the interpretive center is organized and the functions that each staff will have on the site. The direction contains the directions that this interpretive center has during its operation and in control two sheets have been created where the first sheet is to control the entrance of tourists with the collection of important information of the visitors while the second sheet is for the control of employees, Finally, an analysis was made because the interpretive center is located within the facilities of the Torre Loma Tourist Services Association, which is a legal association according to the Organic Law of Popular and Solidarity Economy. In the cost and social analysis, an analysis of the costs of the activities, management, restoration and equipment of the interpretive center was carried out; at the social level, the center will have a high positive impact and viability of the interpretive center.